THU0164 Tnf-Alpha Bioactivity: A New Biomarker of Aspa Activity in Patients with Tnf-Alpha Blockers. (10th June 2014) - Constant, E.; Rinaudo-Gaujous, M.; Amouzougan, A.; Pallot-Prades, B.; Collet, P.; Thomas, T.; Paul, S.; Marotte, H.
Abstract : Background: Infliximab is a chimeric monoclonal antibody targeting tumor necrosis factor alpha (TNFα) indicated in active axial sponsyloarthritis (aSpA). Objectives: We determine association between blood levels of infliximab, antibodies toward infliximab (ATI), TNFα, or TNFα activity with aSpA activity. Methods: In a monocentric cros-sectional study, 49 aSpA patients treated with infliximab were involved. All aSpA patients are the main characteristic of aSpA with 75.5% men, with a mean age of 44 years old (from 16 to 62) treated since 42.4 months (from 0 to 104). Thirteen patients received also methotrexate. Disease activity was assessed by Ankylosing Spondylitis Disease Activity Score (ASDAS). TNFα, infliximab, and ATI serum concentrations were measured in the blood collected before the following infliximab infusion by enzyme-linked immunosorbent assay (LisaTracker, BMD, France). On the same blood collection, TNFα activity was assessed by a bioassay based on induction of IL-6 in response to TNFα. Parametric and non-parametric correlations were performed respectively with Spearman test. Kruskall–Wallis one-way analysis of variance (ANOVA) test was also performed, followed by Dunnett's multiple comparison post hoc tests. For all statistical analysis, P<0.05 was chosen as the level of significance. Results: TNFα at the protein and bioactivity levels strongly correlated together and with aSpA activity according to ASDAS or BASDAI. However, TNFα at the protein level was not correlated with infliximab level, whereas TNFα bioactivity negatively correlated with infliximab level. ATI strongly negatively correlated with infliximab level. Significant level of ATI (>200 ng/mL) was observed in 3 aSpA patients. One had an active disease, whereas the 2 other had a very active disease according to ASDAS values. All of these 3 patients had a low blood level of infliximab (<2 μg/mL). TNFα bioactivity was similar in patients with low infliximab level in presence or not of ATI. Conclusions: In aSpA patients treated with infliximab, TNFα at the protein and bioactivity level are associated with disease activity. In our cohort, only 6% (3/49) patients developed ATI, which is low compared to percent expected in rheumatoid arthritis. Our data suggests that TNFα bioactivity could be a biomarker of aSpA activity in patients with TNFα blockers. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5628